Modelagem Fuzzy como ferramenta para identificação de heurística e vieses cognitivos no processo de tomada de decisão do empreendedor social - Sigette, Elaine Ribeiro (2017)
The mental process for decision making can often present shortcuts that lead to errors that deeply interfere with the individual's perception of the world and the way that individual acts. This issue is even more relevant when we focus on social entrepreneurs and their decision-making process based predominantly on intuition and experience. In order to create a monitoring tool for this process, this paper presents a proposal for the identification of heuristics and cognitive biases using Fuzzy logic as a tool for modeling and data analysis. Once the profile is identified, it is possible to target these entrepreneurs more appropriately in relation to their undertakings. This model can be used by coaches, tutors, consultants, for a direction of their work with the entrepreneurs. For the study of cognitive entrepreneurship in the social economy, both the experiments and the questionnaires were adequate to the target audience as others were created. The result of the analysis of the heuristic profile in the decision making is presented through the index resulting from the defuzzification. After the identification and classification of the profiles it is recommended to use administration tools to mitigate the effects.